Effect of bundle set interventions on physiologic alarms and alarm fatigue in an intensive care unit: A quality improvement project. (December 2021) - Seifert, Micah; Tola, Denise H.; Thompson, Julie; McGugan, Lynn; Smallheer, Benjamin
Abstract: Objective: To determine if the implementation of an evidence-based bundle designed to reduce the number of physiologic monitor alarms reduces alarm fatigue in intensive care nurses. Design: This quality improvement project retrospectively reviewed alarm data rates, types, and frequency to identify the top three problematic physiologic alarms in an intensive care unit. An alarm management bundle was implemented to reduce the number of alarms. The Nurses' Alarm Fatigue Questionnaire was used to measure nurses' alarms fatigue pre- and post-implementation of the bundle. Setting: A combined medical surgical intensive care unit at an accredited hospital in the United States. Results: The top three problematic alarms identified during the pre-implementation phase were arrhythmia, invasive blood pressure, and respiration alarms. All three identified problematic physiologic alarms had a reduction in frequency with arrhythmia alarms demonstrating the largest decrease in frequency (46.82%). When measuring alarm fatigue, the overall total scores increased from pre- (M = 30.59, SD = 5.56) to post-implementation (M = 32.60, SD = 4.84) indicating no significant difference between the two periods. Conclusion: After implementing an alarm management bundle, all three identified problematic physiologic alarms decreased in frequency. Despite the reduction in these alarms, there was not a reduction in nurses' alarm fatigue.